The Influence of Invesment Knowledge and Return Investment on Student's Investment Interest in Investment Banking Products - Lilis Nur'aisyah; Eriswanto, Elan (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
This research aims to examine the influence of investment knowledge and investment returns on students' investment interest in banking investment products. This research used a simple random sampling technique on 96 students in Sukabumi to reveal interest in investing in banking products. The associative quantitative approach in this research uses SPSS V.27 software in the processing process. Primary data was collected through a questionnaire using Google Form. The research results show that partially investment knowledge does not have a significant effect on students' investment interest in banking investment products, while investment returns have a significant effect on students' investment interest in banking investment products. Simultaneously, investment knowledge and investment returns have a significant influence on students' investment interest in banking investment products.